A Test of the Relationships among Perceptions of Justice, Job Satisfaction, Affective Commitment and Organizational Citizenship Behavior - Harif Amali Rifai (Gadjah Mada International Journal of Business, 2005)
This study examines factors influencing organizational citizenship behavior in an organization. These factors include procedural justice, distributive justice, job satisfaction and commitment. Although previous studies have investigated commitment as antecedent of OCB, most of them did not specifically explain the type of commitment hypothesized. In terms of commitment, this study utilizes the specific type of commitment, i.e. affective commitment. The theoretical model proposes both distributive justice and procedural justice as antecedents of job satisfaction and job satisfaction has an effect on organizational citizenship behavior (OCB) through affective commitment. SEM analysis of survey data from 383 nurses who are working for private hospitals in Indonesia supports that the theoretical model has met goodness-of-fit criterions. The findings concluded that there are significant relationships between both procedural justice and distributive justice and job satisfaction. Job satisfaction has a significant impact for developing affective commitment. The results also support that affective commitment is a significant predictor of organizational citizenship behavior.